Green synthesis of Novel Schiff bases derived from 2, 6 diamino pyridine – Characterization and Biological activity - Bhai.R, Devika; Girija, C.R; Reddy.K, Ramakrishna (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Present work produces an excellent green route for the synthesis of Schiff bases derived from 2, 6 diamino pyridine, by using lemon juice as the catalyst. This method is experimentally simple, quick, clean and high yielding. Purity and yield of the reaction is increased by using lemon juice there by avoided the traditional dehydrating agents like glacial acetic acid. This method was successfully extended for the synthesis of different Schiff bases derived from 2,6 diamino pyridine like N,N´-bis(2-hydroxy-1-napthalene)-2,6-pyridiamine, N,N´-bis(2-methoxy-1-napthalene)-2,6-pyridiamine and N,N´-bis (naphthalene)- 2,6-pyridiamine. These compounds were prepared by using catalytic amount of lemon juice, and found more economical, safe, neat and eco friendly than using other commercially available dehydrating agents. The synthesized compounds were characterized by FT-IR, 1HNMR spectroscopy, CHN analysis and mass. Compounds are screened for their antifungal activity against Aspergillusniger and M.fufur while antibacterial activity was checked against E.coli, Klebsiella, Bacillus cereus and Staphylococcus aureus. Hydroxyl derivative of the compound was showing significant anti bacterial activity against all selected bacteria. Klebsiella was showing a considerable inhibition compared to standard Tetracycline.